Coupled monolithic columns as an alternative for the use of viscous ethanol-water mobile phases on chromatographic fingerprinting complex samples - Funari, Cristiano Soleo [UNESP]; Cavalheiro, Alberto Jose [UNESP]; Carneiro, Renato Lajarim (Soc Brasileira Farmacognosia, 2018)
Concepts of sustainability have received attention from people involved in investigation of nature-derived matrices. The effects of concomitant pollutant activities are cumulative and harmful to the environment from which these matrices are obtained. High performance liquid chromatography analyses generate millions of litters of chemical waste worldwide every year. Reduction of organic solvent consumption during the analyses and replacement of harmful solvents with greener options are the main approaches to mitigate this problem. This work explored the strategy of employing monolithic columns when the problematic acetonitrile is intended to be replaced with the greener but more viscous ethanol in fingerprinting a leaf extract of Lippia sidoides Cham., Verbenaceae, by high performance liquid chromatography. Two monolithic columns were coupled in series to test a more critical backpressure condition while doubling the number of theoretical plates, which can be useful to separate the hundreds of compounds present in plant extracts. All work was conducted by employing design of experiments. A mathematical model indicated an optimum point in which ethanol was the only organic solvent of the mobile phase. However, the use of a proper metric, which considered environmental parameters together with separation parameters, evidenced that an experimental condition of the original central composite design should be preferred over the former even if containing 20% acetonitrile in the organic modifier mixture. Flow rates of up to 3 ml/min were accommodated with two coupled monolithic columns without exceeding 250 bar. These findings reinforced that no state-of-the-art instruments are needed to shift from traditional harmful solvents to greener ones, but only require a shift in researchers' approach toward sustainability. (C) 2018 Sociedade Brasileira de Farmacognosia. Published by Elsevier Editora Ltda.
Keywords: Experimental design; Chromatographic fingerprint; Green analytical chemistry; Green solvents; HPLC